Blockchain Based Registration Model for Higher Education - Megha Upreti; Marviola Hardini; Rissa Rahmania; Chandra Abianto (IAIC Bangun Bangsa, 2021)
Education is one of the activities carried out by students and students in order to obtain a title. The process that is common in edification method in Indonesia is a legal action that is done via academic credit at school institutions and must be completed if you want to get recognition in the issuance of a diploma. In Indonesia, a learning activity is full of semi-computer processes but not all educational institutions have implemented this technology. In cases like this, an individual may look for loopholes to commit fraud, such as falsifying diplomas. To find a solution to the problems above, we need to digitize, what is it? Digitization is one of the system that can offer a sense of security and can minimize bureaucracy in the document legal action of ratification with savings on retention and manpower used. A tips passed by students before receiving an academic diploma at one of the universities are starting with the registration process, after all the registration processes are completed, a student is officially accepted at the university and can directly participate in teaching and learning activities , at the time of graduation, it is certain that a student must pass all courses and have completed all the tasks that have been given until he is officially declared graduated. Problems that often occur in the field of education, especially when it is in the registration process, are data falsification, data manipulation, and even the worst case is data loss, this fraud is usually carried out by irresponsible parties. This journal aims to submit a proposal for the schoolboy registry process of school institute in digitalization education method in Indonesia using Blockchain technology. This study resulted in a student enrollment model in an educational institution using Blockchain to supply transparent and validated data in educational process.